Results of numerical modeling of collisionless diffusion induced by electrostatic fluctuations - Khvesyuk, V.I.; Chirkov, A.Yu.; Ryzhkov, S.V. (Вопросы атомной науки и техники, 2003)
Collisionless particle transport is considered on the base of interaction of plasma particles with wave packets arising as a result of the overlap of many wave modes. Results of calculation of diffusion coefficients are presented for different plasma parameters and parameters of magnetic configuration (plasma temperature, magnetic field value, wave amplitudes, etc.). Low frequency and lower hybrid drift waves are considered. Diffusion coefficients coefficients are obtained as results of averaging over sets of particle trajectories and particle energies. Беззіштовхувальна дифузія розглядається з позиції взаємодії частинок плазми й хвильових пакетів , що виникають внаслідок перекриття багатьох хвильових мод. Для різних значень параметрів плазми й магнітної конфігурації (температури плазми, значення магнітного поля, амплітуди хвиль тощо) представлені результати розрахунків коефіцієнтів дифузії. Коефіцієнти дифузії були отримані в результаті усереднення по траєкторіям та енергіям частинок. Бесстолкновительная диффузия рассматривается на основе взаимодействия частиц плазмы и волновых пакетов, возникающих в результате перекрытия многих волновых мод. Для различных значений параметров плазмы и магнитной конфигурации (температура плазмы, величина магнитного поля, амплитуды волн и т.д.) представлены результаты расчетов коэффициентов диффузии. Коэффициенты диффузии были получены в результате усреднения по траекториям и энергиям частиц.